Impairment of the autophagy–lysosomal pathway in Alzheimer's diseases: Pathogenic mechanisms and therapeutic potential - Zhang, Wei; Xu, Chengchao; Sun, Jichao; Shen, Han-Ming; Wang, Jigang; Yang, Chuanbin (Acta pharmaceutica Sinica. B, 2022)
Alzheimer's disease (AD), the most common neurodegenerative disorder, is characterized by memory loss and cognitive dysfunction. The accumulation of misfolded protein aggregates including amyloid beta (Aβ) peptides and microtubule associated protein tau (MAPT/tau) in neuronal cells are hallmarks of AD. So far, the exact underlying mechanisms for the aetiologies of AD have not been fully understood and the effective treatment for AD is limited. Autophagy is an evolutionarily conserved cellular catabolic process by which damaged cellular organelles and protein aggregates are degraded via lysosomes. Recently, there is accumulating evidence linking the impairment of the autophagy–lysosomal pathway with AD pathogenesis. Interestingly, the enhancement of autophagy to remove protein aggregates has been proposed as a promising therapeutic strategy for AD. Here, we first summarize the recent genetic, pathological and experimental studies regarding the impairment of the autophagy–lysosomal pathway in AD. We then describe the interplay between the autophagy–lysosomal pathway and two pathological proteins, Aβ and MAPT/tau, in AD. Finally, we discuss potential therapeutic strategies and small molecules that target the autophagy–lysosomal pathway for AD treatment both in animal models and in clinical trials. Overall, this article highlights the pivotal functions of the autophagy–lysosomal pathway in AD pathogenesis and potential druggable targets in the autophagy–lysosomal pathway for AD treatment. Multiple factors including gene mutations impair autophagy–lysosomal pathway, and exaggerate AD progression. Enhancing autophagy can reduce Aβ levels, promote pathological tau degradation and thus is a promising therapeutic strategy for Alzheimer's disease. [Display omitted]